Газар тариалангийн соёл Өвөр Монгол нутаг дахь нүүдэл соёлд нөлөөлсөн түүхийн зарим асуудалд (Journal of International Studies, 2004)
English title: Some historical problems of influence of agrarian culture on nomadic culture in Inner Mongolia